INTERNET IS ONE MEDIUM THAT CAN BE USED IN TEACHING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) COURSES ONLINE ORIENTED BY USING BLOGGER - Safitri, Baiq Rina Amalia (IKIP Mataram, 2016)
Internet is one medium that can be used in teaching information and communication technology (ICT) courses at IKIP Mataram. The goal of this research is that students are able to develop distance learning tools based on the development of information and communication technology (ICT) through the use of computers, the internet, and other software to support the practicum. This research is classified into development research. Samples of this research were the students of IKIP Mataram who take ICT courses. Outcomes of the study are: (1) a models of learning modules on the internet ICT courses - online oriented by using blogger, (2) a model of learning modules on the internet ICT courses - online oriented in a blog engine form by utilizing blogger, and (3) the publication of the article in the jurnal.